ANALISIS DAN PERANCANGAN SISTEM PEMASARAN DA PEMESANAN PADA DISTRO ”STRONGLIKEASTRONOT ” BERBASIS INTERNET (Information Technology and Telematics, 2013)
Business competition distributions in Semarang are getting tighter. StrongLikeAstronot is one of the new distro was founded in 2011 in Semarang. The mechanism of the distribution system sales StrongLikeAstronot today still market their products through social networking. Sales information on the distribution system "StronglikeAstronot" is part of a marketing information system, which was developed to collect, process and store sales data so that the data can be retrieved to be distributed as an information berguna.wujud of sales information system is to produce applications E -commerce. With the application of E-Commerce on the distro "StrongLikeAstronot" is expected to provide facilities for the public to purchase the product, as well as expand the sales market distributions "StrongLikeAstronot". This distribution was developed by the SDLC (System Development Life Cycle). As for the software used to design and design the application of e-commerce programming language PHP, Macromedia Dreamweaver CS5 text editor and MySQL database. Application Information Systems generated sales transaction data is able to manage the sale of goods, data items, and data buyers or consumers, as well as generate reports complete, accurate and always actual. These reports include sales report, the financial report. Kata Kunci : sistem penjualan, e-commerce, aplikasi e-commerce distro, PHP dan MySQL